2008
DOI: 10.1111/j.1468-1293.2008.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cholecalciferol supplementation on vitamin D levels and insulin sensitivity is dose related in vitamin D‐deficient HIV‐1‐infected patients

Abstract: ObjectiveThe aim of this study was to explore the effects of cholecalciferol supplementation on vitamin D levels, bone mineral density (BMD), body fat distribution and insulin sensitivity in vitamin D-deficient HIV-1-infected patients. MethodsTwenty vitamin D-deficient HIV-1-infected patients were prospectively treated with 2000 IU cholecalciferol/day for 14 weeks, whereafter treatment was continued with half this dosage until 48 weeks. BMD, body fat distribution, 1,25-dihydroxy vitamin D 3 (1,25(OH) 2 D 3 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
0
13
2
Order By: Relevance
“…It is suggested that 25OH-vitamin D levels should even be supplemented to >75 nmol/L [31]. Even if the results of studies regarding fractures rate in HIV-patients yielded conflicting results and the effect of cholecalciferol is uncertain [32-36], we actually suggest cholecalciferol supplementation. We observed a decrease in bone resorption as well as bone formation markers 3 month after supplementation.…”
Section: Discussionmentioning
confidence: 85%
“…It is suggested that 25OH-vitamin D levels should even be supplemented to >75 nmol/L [31]. Even if the results of studies regarding fractures rate in HIV-patients yielded conflicting results and the effect of cholecalciferol is uncertain [32-36], we actually suggest cholecalciferol supplementation. We observed a decrease in bone resorption as well as bone formation markers 3 month after supplementation.…”
Section: Discussionmentioning
confidence: 85%
“…Supplementation with cholecalciferol requires at least 2000 IU/day for 14 days followed by 1000 IU/day thereafter to normalize vitamin D levels. Despite this supplementation there was no effect on BMD at 48 weeks in a small pilot study [38].…”
Section: Vitamin D Deficiencymentioning
confidence: 96%
“…The authors attributed this finding to the low prevalence of osteopenia and osteoporosis at baseline among their participants. 178 Similarly, Mondy and colleagues, 179 in a cohort of 31 participants originally enrolled in an RCT powered to detect lumbar spine BMD change with the use of alendronate, showed that among subjects randomized to receive only calcium 1 g/day plus vitamin D 400 IU daily, lumbar spine BMD increased by 1.3% at 48 weeks compared with baseline (vs 5.2% in the alendronate group). This change, however, was not statistically significant.…”
Section: Benefits Of Vitamin D Supplementationmentioning
confidence: 92%
“…A smaller prospective study in the Netherlands also failed to demonstrate benefit of vitamin D supplementation on insulin resistance and inflammatory markers (ie, IL-6, TNF-a) after 48 weeks. 178 In an RCT involving 52 mostly virologically suppressed vertically infected youths aged 8 to 26 years with 25-OHD less than 30 ng/mL, Giacomet and colleagues 188 showed that 12-month supplementation with cholecalciferol 100,000 IU every 3 months for 4 doses resulted in an anti-inflammatory T-cell phenotype (ie, decrease in Th17:Treg ratio) at 3 months. This effect was no longer seen at 12 months.…”
Section: Other Effectsmentioning
confidence: 97%